GhCDPK60 positively regulates drought stress tolerance in both transgenic Arabidopsis and cotton by regulating proline content and ROS level - Yan, Mengyuan; Yu, Xiaotian; Zhou, Gen; Sun, Dongli; Hu, Yu; Huang, Chenjue; Zheng, Qintao; Sun, Nan; Wu, Jiayan; Fu, Zhaobin; Li, Libei; Feng, Zhen; et al. (Frontiers in Plant Science, 2022)
Calcium-Dependent Protein Kinases (CDPKs) involved in regulating downstream components of calcium signaling pathways play a role in tolerance to abiotic stresses and seed development in plants. However, functions of only a few cotton CDPKs have been clarified at present. In this study, 80 conserved CDPKs in Gossypium hirsutum L. were identified and characterized, which was divided into four subgroups. Among them, the transcript level of GhCDPK60 was significantly upregulated under drought and several hormone treatments. And we found that the expression levels of several stress-inducible genes down-regulated in GhCDPK60-silence cotton and up-regulated in GhCDPK60-overexpressing Arabidopsis. In addition, physiological analyses demonstrated that GhCDPK60 improved drought stress tolerance by improving the osmotic adjustment ability and reducing the accumulation of reactive oxygen species (ROS) in plants. These findings broaden our understanding of the biological roles of GhCDPK60 and mechanisms underlying drought stress tolerance in cotton.